Research through design in urban and landscape design practice - Cortesão, João; Lenzholzer, Sanda (Journal of urban design, 2022)
This study takes stock on how research through design (RTD) is interpreted in urban and landscape design practice in relation to the scholarly meaning of RTD. The results indicate that the term 'RTD' in Dutch practice largely refers to the typical procedures and resources of a practical design process. This interpretation differs from definitions of scholarly RTD which have more focus on the rigid testing of design alternatives. Such a scholarly RTD approach is advisable to ensure the validity and robustness of design products. This study recommends that this approach to RTD is adopted in urban and landscape design practice.